Comparison of methods to estimate the affected body surface area and the dosage of topical treatments in psoriasis and atopic dermatitis: the advantage of a picture‐based tool. (5th June 2019) - Speeckaert, R.; Hoorens, I.; Corthals, S.; Delbaere, L.; Lambert, J.; Lesseliers, T.; Mylle, S.; Ongenae, K.; De Schepper, S.; De Smet, L.; Speeckaert, M.; van Geel, N.
Abstract: Background: The accurate determination of the dosage of topical treatments is important given its repercussions on patient adherence and therapeutic efficacy. Up till now, the fingertip unit calculated by the rule of hands is considered the gold standard, although its use is associated with several drawbacks. Objective: To compare different methods to estimate the affected body surface area (BSA) and dosage of topical treatments in atopic dermatitis and psoriasis and investigate its reliability, user‐friendliness and timing. Methods: In this study, we compared the reliability of three different methods: (i) the fingertip unit calculated by the 1% hand rule; (ii) a picture‐based tool [termed Cutaneous Inflammatory Disease Extent Score (CIDES)]; and (iii) a digital drawing tool. Eleven observers scored 40 patients with psoriasis and eczema to assess the inter‐rater and intrarater reliability. Timing was automatically recorded, and user‐friendliness was investigated by a questionnaire. Results: An excellent intraclass correlation (ICC) was found for both inter‐rater agreement and intrarater agreement for the picture‐based tool (ICC = 0.92 and ICC = 0.96, respectively). The ICCs for drawing the area of involvement on a silhouette were 0.89 and 0.93, respectively. Finally, the rule of hands was associated with an increased inter‐rater variability although an excellent intrarater agreement was found (ICC = 0.79 and 0.95, respectively). Automated calculation of the amount of topical treatment improved reliability, and CIDES was associated with the least variation. CIDES was considered the preferred method by all observers and was fast to perform (median: 30 s). Conclusion: A picture‐based method offered the most advantages (in terms of reliability, speed and user‐friendliness) to estimate the affected BSA and calculate the dosage of topical treatments.